Radar electronic warfare - Golden, August (American Institute of Aeronautics and Astronautics, 1987)
Annotation This text provides readers with a solid foundation for understanding electronic countermeasures. It defines common terms and principles used in the fields of radar and electronic warfare and describes the response of radar systems to electronic countermeasures. In-depth analyses of the effects that various electronic countermeasure emissions have on classes of radar systems follows.
Keywords: Radar -- Military applications.; Electronics in military engineering.; Avionics.; elektronické knihy; electronic books